Performance of outdoor seawater treatment systems for recirculation in an intensive turbot (Scophthalmus maximus) farm - Borges, Maria Teresa (2011)
Water treatment systems are mandatory in recirculating aquaculture facilities facing existing regulations, but data on system efficiency, especially for marine species, are scarce. The present work aimed at contributing to the evaluation of the effluent characteristics and the performance of a combined outdoor biological and non-biological treatment system in an intensive turbot (Scophthalmus maximus) farm, operating under different hydraulic regimes. A preliminary study on the biofilter bacterial populations was also undertaken. Changes in effluent characteristics with pumping, season of the year and fish biomass were observed. The treatment system showed performance instability under the conditions assayed (outdoors, changeable recycle rates). Maximum removal of solids was observed in winter, with microscreen or biological filtration (up to 60%) and nitrite removal (40–98%) was achieved with ozonation. Reduction in ammonium levels was higher in summer, either mechanically (74%) or biologically (33%). Phosphate removal was higher in winter with both systems (37 and 60%, respectively). Compliance with Portuguese discharge standards was achieved. For improvements in the treatment loop, further studies on biofilter bacteria under outdoor conditions are needed, and biological denitrification is encouraged.